2019
DOI: 10.1186/s12885-019-6058-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national perspective of migration and cancer: incidence of five major cancer types among resettlers from the former Soviet Union in Germany and ethnic Germans in Russia

Abstract: Background Few studies compared cancer incidence among migrants both to their host countries and to their population of origin. We aimed to compare cancer incidence of ethnic Germans who migrated from the former Soviet Union to Germany (resettlers) to those living in Russia as well as to the German and the Russian general populations. Methods The cancer registry of North Rhine-Westphalia identified incident cases of stomach, colorectal, lung, breast and prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The overall share of German citizens with a migrant background in the total population amounts to 13.4% [ 5 ]. Interestingly, one study analyzed the cross-national prospective of cancer incidences among ethnic Germans who migrated from the former Soviet Union to Germany (also named as resettlers) and those residing in Russia, and concluded that the incidence among migrant populations often remains the same between the population of origin and the new host community [ 6 , 7 ]. Given that Germany is home to ~ 4 million people with Turkish roots, Spallek et al found in a similar cross-national study that cancer of the respiratory organs is diagnosed less frequently in Turkish men in older birth cohorts, whereas it is more frequent in younger birth cohorts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall share of German citizens with a migrant background in the total population amounts to 13.4% [ 5 ]. Interestingly, one study analyzed the cross-national prospective of cancer incidences among ethnic Germans who migrated from the former Soviet Union to Germany (also named as resettlers) and those residing in Russia, and concluded that the incidence among migrant populations often remains the same between the population of origin and the new host community [ 6 , 7 ]. Given that Germany is home to ~ 4 million people with Turkish roots, Spallek et al found in a similar cross-national study that cancer of the respiratory organs is diagnosed less frequently in Turkish men in older birth cohorts, whereas it is more frequent in younger birth cohorts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, resettlers exhibit lower all-cause mortality and a lower mortality from cardiovascular disease compared with the general population [ 15 ]. Research on the health of ethnic Germans in Russia is limited to one study that compared cancer incidence between ethnic Germans and the general population in the district of Tomsk, Russia [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…They observed a better outcome of rst-generation non-Western immigrants compared with Western patients. Meanwhile, research in Germany has concentrated on speci c ethnic groups: Jaehn et al [7,8] investigated etiologic differences and incidence rates among migrants from the former Soviet Union and the general population in Germany. Their conclusion is that cancer incidence among migrant populations shows a transition of incidence rates of their country of origin to incidence rates of their new host country.…”
Section: Introductionmentioning
confidence: 99%